Home Bias in Equity Portfolios, Inflation Hedging, and International Capital Market Equilibrium - Cooper, Ian; Kaplanis, Evi (Review of Financial Studies, 1994)
We test whether the home bias in equity portfolios is caused by investors trying to hedge inflation risk. The empirical evidence is consistent with this motive only if investors have very high levels of risk tolerance and equity returns are negatively correlated with domestic inflation. We then develop a model of international portfolio choice and equity market equilibrium that integrates inflation risk and deadweight costs. Using this model we estimate the levels of costs required to generate the observed home bias in portfolios consistent with different levels of risk aversion. For a level of risk aversion consistent with standard estimates of the domestic equity market risk premium, these costs are about a few percent per annum, greater than observable costs such as withholding taxes. Thus, the home bias cannot be explained by either inflation hedging or direct observable costs of international investment unless investors have very low levels of risk aversion.